Problems of Gender Policy in Ukraine and Western Europe: Сomparative-Historiographical Analysis - Inna Strazhnikova (Pedagogical Discourse, 2018)
The current Constitution of Ukraine provides equal rights for men and women in all spheres of social life, but in reality the advantage remains on the side of men. One should only mention such spheres of life as family, politics and business (especially big business), where the representatives of the strong half of mankind play a dominant role in our time. Ago, the article analyzes the views of Ukrainian and scholarly other countries on the gender education of student youth as a socio-pedagogical problem, reveals the common and different in the methodology of gender pedagogy, mechanisms of implementation of the gender approach in the educational space. The author reveals the main strategies for the implementation of gender education of German youth, youth in the Great Britain and Ukraine, analyzes the gender orientation of vocational guidance work among the youth of certain countries, the peculiarities of the functioning and adoption of the principles of gender education inseparable from educational processes, raising the general gender culture of society, and deepening the gender competence of teachers through the internal ‑ and their externally raising their qualifications. The features of the gender education process in the German schools of different types and in schools of Great Britain, in particular in elementary and primary schools, are specified, implementation of the content, forms, methods and methods of gender education is specified; the peculiarities of the historical development of the educational system in Germany are determined, the ways of the formation of gender education of the student youth of Germany at the present stage, which is carried out through joint, separate and partly separate education, are specified.The introduction of a gender component to the Ukrainian educational system is the introduction of respect for the dignity of each person, the lack of stamps on materials and textbooks on the implementation of certain social roles.